Influence of heat treatment on the microstructure and tensile properties of 420 stainless steel febricated by laser powder bed fusion - Sepako, Motheo (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2025.